Bismuth-based Brillouin/erbium fiber laser - Shahabuddin, Nurul Shahrizan; Harun, Sulaiman Wadi; Zulkifli, Mohd Zamani; Thambiratnam, K.; Ahmad, Harith (Taylor & Francis, 2008)
A multi-wavelength Brillouin/erbium-doped fiber laser (BEFL) operating in the 1573 nm region is proposed and demonstrated. The system employs both linear and nonlinear gain from a bismuth-based erbium-doped fiber (Bi-EDF) approximately 215 cm long and a single mode fiber (SMF) of various lengths to generate an optical comb with a spacing of approximately 0.089 nm. Two 3 dB couplers were used to form a looping arm in the system in order to produce cascaded Brillouin Stokes waves as internal feedback for multi-wavelength operation. A stable output laser comb with 10 lines at more than -13 dBm was obtained with 4.85 dBm Brillouin pump power and two 140 mW pumps at 1480 nm. The 1480 nm pumps' power and SMF length have a significant effect on the number of wavelengths and on the output power of the generated wavelength comb.